CLASSROOM SIMULATION METHOD INCREASES NURSING STUDENT FAMILY-FOCUSED CARE COMPETENCIES IN FAMILY NURSING LEARNING PRACTICE - Stefanus Mendes Kiik; Mahathir Mahathir; Juli Dwi Prasetyono (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Nursing is a professional field that requires formal education and institutional learning experiences in acquiring specific expertise. Family nursing is one of the core science in nursing education that requires a specific approach in order to build a professional nurse-family relationship. Family-focused care education demand a broader understanding in providing care of  the family as a unit system by the students to meet the family needs. Educators should choose effective and creative learning methods in teaching the important component of family-focused care. Classroom simulations is a method that considered to be able to accommodate the achievement of cognitive, psychomotor, caring and nursing process. This study was conducted to identify the effectiveness of classroom simulation learning methods to student family-focused care competencies using family-focused care competency assessment by Van Gelderen rubric. This research was conducted by quasi experimental pre and post with control group design. The sample size is done by hypothesis test two pairs population (numeric data) formula. The study was conducted on 34 respondent as a sample that showed significance increasing of the mean value after classroom simulation Man Whitney test (p = 0.000). It is sugested the application of clasroom simulation learning methods before the students perform nursing practice directly to the family. Van Gelderen rubric is an instrument which is able to assess the competence of family-focused care.Keywords : Simulation, classroom simulation, nursing education, family nursing, family-focused care.